Importance of Patient Education for At-home Yoga Practice in Women With Hormonal Therapy-induced Pain During Adjuvant Breast Cancer Treatment: A Feasibility Study. (December 2021) - Faravel, Kerstin; Huteau, Marie-Eve; Jarlier, Marta; de Forges, Hélène; Meignant, Laetitia; Senesse, Pierre; Norton, Joanna; Jacot, William; Stoebner, Anne
Background: Osteo-articular pain (OAP) is experienced by approximately 50% of women under hormonal therapy (HT) for breast cancer (BC), which increases the risk for therapy discontinuation. This study was aimed to assess benefits of yoga practice combined with patient education (PE) for at-home practice by evaluating feasibility among BC patients under HT and measuring OAP, flexibility and satisfaction. Methods: Feasibility was evaluated by patient adherence as accomplishment of at least 4 out of 6 supervised yoga-PE sessions along with 70% or more at-home yoga sessions. Intervention (12 weeks) included two 6-weeks periods: P1 comprising one 90-minutes supervised yoga-PE session/week and 15-minutes daily at-home yoga and P2, daily autonomous at-home yoga sessions. Evaluations (at inclusion and by the end of each period) consisted in assessment of OAP on Visual Analog Scale (VAS), forward flexibility (cm) and patient satisfaction on Likert (0-10 points) scale. Results: Between September 2018 and May 2019 we included 24 patients of median 53 years (range 36-72). Feasibility was validated by 83% successful adherence rate. Pain was significantly reduced from median VAS of 6 [range 4-10] to 4 [range 0-7] at the end of both P1 and P2 ( p  < 0.01), albeit with no difference between P1 and P2. Forward flexibility improved by a median gain of 8 cm (end of P2) and median satisfaction score of 10/10 [range 8-10]. Conclusion: Combined physiotherapy-yoga-PE intervention is a feasible strategy to increase at-home yoga practice with potential benefit on pain, flexibility, and satisfaction, thus prompting further evaluations in larger randomized multicenter trials. ClinicalTrials.gov: NCT04001751